Development Design of Millennial Road Safety Festival Program in North Sulawesi Regional Police - Vita Mayastinasari; Benyamin Lufpi (Journal of Indonesia Road Safety, 2020)
One of the current programs to realize security, safety, order, and smooth traffic is the Millennial Road Safety Festival (MRSF). The focuses of problems in this research are respondents' views on "Police Goes to School (PGTS) and the proposal of the development design of MRSF. The outputs are the realization of security, safety, order, smooth traffic, and performance of police institutions. The approach used a mixed-method with survey and questionnaire distribution, interview, and document study. The respondents were junior and senior high school students who had never and ever participated in PGTS. The informants were the Principal, Teachers, the administration staff, chief of Departmental Police, deputy chief of Departmental Police, and chief of Traffic Unit, and the traffic unit personnel. The development of MRSF is integrated through four methods: management of road safety knowledge, empowering personnel in traffic functions and millennial communities, the synergy between duty bearers with road safety, and control of the program. ABSTRAK Saat ini salah satu program untuk mewujudkan keamanan, keselamatan, ketertiban, dan kelancaran lalu lintas adalah Millennial Road Safety Festival (MRSF). Fokus permasalahan dalam penelitian ini adalah terkait pandangan responden tentang “Police Goes to School (PGTS) dan Usulan Rancangan Pembangunan MRSF. Outputnya adalah terwujudnya keamanan, keselamatan, ketertiban, kelancaran lalu lintas, dan kinerja institusi kepolisian. Pendekatan yang digunakan adalah metode campuran dengan survei dan penyebaran kuesioner, wawancara, dan studi dokumen. Responden adalah siswa SMP dan SMA yang belum pernah dan pernah mengikuti PGTS. Informannya adalah Kepala Sekolah, Guru, staf administrasi, Kapolda, Wakapolda, dan Kapolres, serta personel unit lalu lintas. Pengembangan MRSF diintegrasikan melalui empat metode: manajemen pengetahuan keselamatan jalan, pemberdayaan personel dalam fungsi lalu lintas dan komunitas milenial, sinergi antara pengemban tugas dengan keselamatan jalan raya, dan pengendalian program.